Writing Hopeful Climate Fiction for Middle Grade Readers - Rupert Barrington (Leaf Journal)
Many children suffer from climate anxiety. How can children’s fiction help them? Through the lens of three Middle Grade novels – The Last Bear by Hannah Gold; A Cloud Called Bhura by Bijal Vachharajani and Where the World Turns Wild by Nicola Penfold – this essay examines the nature of climate anxiety, asks why addressing it for Middle Grade readers is particularly important, and looks at ways in which authors can write hopeful and helpful climate change stories.